Making sense of youth futures narratives: Recognition of emerging tensions in students’ imagination of the future - Barelli, Eleonora; Tasquier, Giulia; Caramaschi, Martina; Satanassi, Sara; Fantini, Paola; Branchetti, Laura; Levrini, Olivia (Frontiers in Education, 2022)
In this era of great uncertainty, imagining the future may be challenging, especially for young people. If in science education the interest in future-oriented education is now emerging, research needs however to keep eyes on youngsters’ future perceptions and on the development of a future literacy. In this paper, starting from a sample of individual students' narratives about their future daily life in 2040, we aim to delineate which ways of grappling with the future ways of grappling with the future can be observed in the essays and which methodological tools are suited to operationalize their identification and characterization. The analysis led to the definition of "polarisation" and "complexification" attitudes that represent the ways in which the students’ narratives are positioned with respect to a bunch of dichotomies: personal-societal, functional-aesthetics oriented, good-bad, natural-artificial, and certain-uncertain. Moreover, with this study, we provide a contribution to the methodological reflection that deals with the collection and analysis of data, when students’ future perceptions need to be investigated. Discussing the limits of the current data collection tool, we introduce the design of a SenseMaker® questionnaire which contributed to feeding a collaboration with #OurFutures project, recently launched by the European Commission to collect future narratives all around Europe.